2021
DOI: 10.18632/aging.202378
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA XIST sponges miR-199a-3p to modulate the Sp1/LRRK2 signal pathway to accelerate Parkinson’s disease progression

Abstract: In vitro and in vivo models of Parkinson’s disease were established to investigate the effects of the lncRNA XIST/miR-199a-3p/Sp1/LRRK2 axis. The binding between XIST and miR-199a-3p as well as miR-199a-3p and Sp1 were examined by luciferase reporter assay and confirmed by RNA immunoprecipitation analysis. Following the Parkinson’s disease animal behavioural assessment by suspension and swim tests, the brain tissue injuries were evaluated by hematoxylin and eosin, TdT-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
(27 reference statements)
0
25
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs) are part of non-coding RNAs with sizes between 200 nucleotides and several kbs and high tissue specificity. They have fundamental role in regulation of gene expression (Zhou et al, 2021 ). According to the Annotations of the FANTOM5 project, about 28,000 lncRNA genes have been identified so far (Hon et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are part of non-coding RNAs with sizes between 200 nucleotides and several kbs and high tissue specificity. They have fundamental role in regulation of gene expression (Zhou et al, 2021 ). According to the Annotations of the FANTOM5 project, about 28,000 lncRNA genes have been identified so far (Hon et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Ewing’s sarcoma, the target regulatory interaction between miR-199a-3p and TUG1 is confirmed [ 27 ]. Increasing evidence has revealed the important role of miR-199a-3p in neurological diseases [ 28–30 ]. MiR-199a-3p is reported to play a protective role in neuron cells in a variety of diseases [ 14 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, low levels of miR-199a-3p were detected in TLE patients, which was negatively correlated with the levels of TUG1. In a study about Parkinson’s disease, miR-199a-3p overexpression can protect against the disease progression via inhibiting neuron cell apoptosis and promoting cell proliferation [ 28 ]. In light of the target relationship of miR-199a-3p with TUG1, we speculated that miR-199a-3p might be involved in the regulatory role of TUG1 in TLE.…”
Section: Discussionmentioning
confidence: 99%
“…LRRK2 gene has been acknowledged to be associated with PD. Researchers found that Hox transcript antisense intergenic RNA (HOTAIR), X-inactive specific transcript (XIST), and metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) indirectly enhanced the expression of LRRK2, which would increase the rate of apoptosis (Wang et al, 2017 ; Chen Q. et al, 2018 ; Zhou Q. et al, 2021 ). HOTAIR may also promote apoptosis of neuronal cells through microRNA-126-5p (miR-126-5p)/RAB3A-interacting protein (RAB3IP) axis (Lin et al, 2019 ).…”
Section: How Do the Ncrnas Regulate Parkinson’s Disease?mentioning
confidence: 99%